Youth underrepresentation as a barrier to sexual and reproductive healthcare access in Kasulu district, Tanzania: A qualitative thematic analysis - Shumbusho Damian, Respicius; Zakumumpa, Henry; Fonn, Sharon (International journal of public health, 2020)
Representation of the key groups in community-level healthcare decisions is a prerequisite for accountable and responsive primary healthcare systems. However, meaningful representation requires both the presence of individuals who represent the key community groups and their capacity to influence the key healthcare plans and decisions. Our study explored how the underrepresentation of the youth in health facility committees, the decentralized community- and facilitylevel healthcare decision-making forums affects youth access to sexual and reproductive health services. Methods A multisite case study involving focus group discussions, interviews, and meeting observation was conducted in eight primary healthcare facilities in Kasulu, a rural district in Tanzania. Inductive thematic analysis was used to identify the key emerging themes. Results Five major themes were identified in connection with youth underrepresentation and limited access to sexual reproductive health as a ‘taboo’ phenomenon in the communities. These were: numbers do not matter, passive representation, sociopolitical gerontocracy, economic vulnerability, and mistrust and suspicion. Conclusions Gradual emancipatory and transformative efforts are needed to normalize the representation of the youth and their concerns in formal community-level decision-making institutions.
Keywords: Youth representation; Sexual and reproductive health; Health facility committees; Healthcare access